60 EVALUATING THE TIME THAT PATIENT'S WITH DEMENTIA/DELIRIUM SPEND IN THE EMERGENCY DEPARTMENT PRIOR TO TRANSFER TO A WARD. (18th November 2021) - Gibbons, C; Diffley, K; Riches, R; Ramiah, V; Byrne, C; Kyne, L; Gaynor, E
Abstract: Background: Patients with dementia and delirium are often waiting long times in the emergency department (ED) prior to being transferred to a ward bed during an acute hospital admission. This may be associated with increased morbidity and mortality. Best practice is for rapid triage to an appropriate bed via a delirium/dementia pathway. Our aim was to document the patient experience time (PET) for older patients with a diagnosis of dementia or delirium in ED in an urban tertiary-referral hospital. Methods: Over a two-week period 07/12/20–21/12/20, we identified all patients admitted under a general medical specialty through ED, aged ≥65 years, with a diagnosis of dementia or delirium on the admission sheet. Patients admitted with a stroke or hip fracture were excluded. ED PET was recorded, as well as final ward destination. Results: We included 29 patients in the study—median age was 82 years (range 71–92); 19 (66%) were female. Delirium was the presenting complaint in 79.31% (n = 23) of cases. Sixteen (55%) patients presented between 8 am-5 pm. The average time spent from triage to ED doctor review was 1 hour 48 minutes; from ED doctor review to medical referral −1 hour 27 minutes; from medical referral to decision for medical admission—2 hours 28 minutes; from decision for medical admission to ward admission- 5 hours. Overall, the average ED PET for these patients was 10 hours 42 minutes. Five patients (17%) were admitted directly to a Specialist Geriatric Ward (SGW). Twenty patients (69%) did not reach a SGW during the study period. Conclusion: Patients with dementia and delirium may spend prolonged periods of time in the ED putting them at risk for multiple complications. We hope that by introduction of a dementia/delirium combined pathway and care bundle that we can reduce PET for these vulnerable patients.